Reconfiguraring Zinā: The Criminalization of Adultery in Modern Egyptian Criminal Law - Abdalgaber Mohamed (Al-Jami'ah: Journal of Islamic Studies, 2025)
The Egyptian parliamentary debates on the criminalization of adultery reveal how Sharīʻa is invoked to penalize conduct that does not correspond to the conceptual foundations, definitions, evidentiary standards, or procedural rules of zinā in Islamic jurisprudence. This article examines how opposing sides in these debates construct their legal arguments and deploy distinct modes of reasoning, each grounding its position in Sharīʻa to justify the penalization of adultery. It asks why Sharīʻa doctrines of zinā are mobilized to legitimize the criminalization of adultery in Egyptian criminal law. The article argues that this strategy generates ambiguity, inconsistency, and doctrinal indeterminacy, while simultaneously undermining the function of modern criminal law within the framework of the modern state. In doing so, it produces a distorted mode of rearticulating Sharīʻa within contemporary legal institutions. Finally, the article contends that any attempt to reclaim Sharīʻa within the modern state must take into account the public function of criminal justice institutions, particularly their role in securing constitutional values such as fairness, non-discrimination, justice, and equality.[Perdebatan parlementer di Mesir mengenai kriminalisasi perzinaan memperlihatkan bagaimana syariat Islam diargumentasikan untuk menghukum suatu perbuatan yang tidak sejalan dengan landasan konseptual, definisi, standar pembuktian, maupun prosedur zinā dalam fikih Islam. Artikel ini mengkaji bagaimana pihak-pihak yang berseberangan dalam perdebatan tersebut membangun argumen hukum mereka dan menggunakan metode penalaran yang berbeda, masing-masing dengan mendasarkan posisinya pada Syariat untuk membenarkan kriminalisasi perzinaan. Pertanyaan utama yang diajukan adalah mengapa doktrin Syariat tentang zinā dimobilisasi untuk melegitimasi kriminalisasi perzinaan dalam hukum pidana Mesir. Artikel ini berargumen bahwa strategi tersebut melahirkan ambiguitas, inkonsistensi, dan ketidakpastian doktrinal, sekaligus melemahkan fungsi hukum pidana modern dalam kerangka negara modern. Dalam prosesnya, hal ini menghasilkan cara yang terdistorsi dalam mengartikulasikan kembali Syariat di dalam institusi hukum kontemporer. Pada akhirnya, artikel ini menegaskan bahwa setiap upaya untuk mereklaim Syariat dalam negara modern harus mempertimbangkan fungsi publik lembaga peradilan pidana, khususnya perannya dalam menjamin nilai-nilai konstitusional seperti keadilan, non-diskriminasi, kesetaraan, dan kepastian hukum.]